Direct measurement of electron sloshing of an inertial Alfvén wave. Issue 10 (18th May 2016) - Schroeder, J. W. R.; Skiff, F.; Kletzing, C. A.; Howes, G. G.; Carter, T. A.; Dorfman, S.
Abstract: We report laboratory measurements of the parallel current carried by suprathermal electrons associated with inertial Alfvén wave excitation in the laboratory. The experiments presented here use a novel wave absorption diagnostic that measures the suprathermal tails of the electron distribution parallel to the mean magnetic field. The diagnostic is used to probe the electron distribution as an inertial Alfvén wave propagates along the mean magnetic field. These results identify, for the first time, the periodic motion of suprathermal electrons participating in the inertial Alfvén wave itself, in agreement with predictions from linear kinetic theory. Key Points: Inertial Alfvén waves have an electric field aligned with the mean magnetic field that is predicted to modify electron motion Laboratory measurements of electron sloshing at the Alfvén wave frequency verify predictions The magnetic field‐aligned electric field of inertial Alfvén waves is also expected to resonantly accelerate auroral electrons